1997
DOI: 10.1007/s004410050851
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ionocytes in the saccular epithelium of the inner ear of two teleosts ( Oncorhynchus mykiss and Scophthalmus maximus)

Abstract: The saccular membranes of trout (Oncorhynchus mykiss) and turbot (Scophthalmus maximus) were examined to characterize specialized epithelial cells that might be responsible for ion exchange. The approach for localizing cell types was new for this tissue, as observations were made with a stereomicroscope and a light microscope in order to have a general view of the epithelium. No important differences between the two species were seen. The saccular tissue is a monolayer epithelium (except for the macula neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 37 publications
4
43
0
1
Order By: Relevance
“…This process has been corroborated by recent studies dealing with the various cellular types of the saccular epithelium (Mayer-Gostan et al 1997; Takagi Illustration of the different zone patterns (black arrow zone 2 postmetamorphic mark; white arrows zone 3 checks; discontinuous double black arrows opaque bands; continuous double black arrows translucent bands; An-Di antero-distal axes) 1997, 2000aPisam et al 1998). Depending on the species, variation in distribution within this epithelium of cellular ionic pumps (Mayer-Gostan et al 1997;Tohse and Mugiya 2001) and of secretory cells (Payan et al , 1999 led to a solute gradient, the formation of which interfered with otolith bio-calcification by favouring deposition on the proximal side (e.g. in turbot, Scophthalmus maximus, Payan et al 1999) or on the otolith edge, as in trout (Oncorhynchus mykiss, Payan et al 1999;Takagi and Takahashi 1999;Takagi 2000b).…”
Section: Inner Ear Otolith Growth and Tridimensional Asymmetrymentioning
confidence: 53%
“…This process has been corroborated by recent studies dealing with the various cellular types of the saccular epithelium (Mayer-Gostan et al 1997; Takagi Illustration of the different zone patterns (black arrow zone 2 postmetamorphic mark; white arrows zone 3 checks; discontinuous double black arrows opaque bands; continuous double black arrows translucent bands; An-Di antero-distal axes) 1997, 2000aPisam et al 1998). Depending on the species, variation in distribution within this epithelium of cellular ionic pumps (Mayer-Gostan et al 1997;Tohse and Mugiya 2001) and of secretory cells (Payan et al , 1999 led to a solute gradient, the formation of which interfered with otolith bio-calcification by favouring deposition on the proximal side (e.g. in turbot, Scophthalmus maximus, Payan et al 1999) or on the otolith edge, as in trout (Oncorhynchus mykiss, Payan et al 1999;Takagi and Takahashi 1999;Takagi 2000b).…”
Section: Inner Ear Otolith Growth and Tridimensional Asymmetrymentioning
confidence: 53%
“…Ionocytes have been found throughout the fish labyrinth (Mayer-Gostan et al, 1997) and have been specifically localized to the wall of the utricle and the common crus in the semicircular canals (Becerra and Anadon, 2003) and the wall of the saccule (Mayer-Gostan et al, 1997). These cells are thought to maintain the ionic gradient between endolymph, perilymph, and cranial fluid and are shown to contain large mitochondria and a membrano-tubular system in which Na ϩ /K ϩ -ATPase is located (Mayer-Gostan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These cells are thought to maintain the ionic gradient between endolymph, perilymph, and cranial fluid and are shown to contain large mitochondria and a membrano-tubular system in which Na ϩ /K ϩ -ATPase is located (Mayer-Gostan et al, 1997). Fish endolymph is typically higher in sodium than is mammalian endolymph, and cranial fluids are normally close in ionic composition to plasma (Mayer-Gostan et al, 1997). This study revealed a significant difference between fish and mammals in the Na ϩ and K ϩ gradients across the hair-cell epithelium and, consistent with previous studies, higher sodium levels in endolymph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations